2019
DOI: 10.1159/000504000
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pituitary and Other Tumours with Cabergoline: New Mechanisms and Potential Broader Applications

Abstract: Cabergoline is a dopamine agonist that has been used as the first-line treatment option for prolactin-secreting pituitary adenomas for several decades. It not only suppresses hormone production from these prolactinomas, but also causes tumour shrinkage. Recent studies revealed some novel mechanisms by which cabergoline suppresses tumour cell proliferation and induces cell death. In this article, we review the most recent findings in cabergoline studies, focusing on its anti-tumour function. These studies sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 133 publications
0
15
0
1
Order By: Relevance
“…Furthermore, iMRI improved GTR rates, which correlated with longer PFS (29). Moreover, some dopamine agonists have shown to be effective for treating residual NFPA, and reduced the recurrence of NFPA (33)(34)(35). These data suggest that it is of great importance to find strategies to predict recurrence.…”
Section: A B Cmentioning
confidence: 88%
“…Furthermore, iMRI improved GTR rates, which correlated with longer PFS (29). Moreover, some dopamine agonists have shown to be effective for treating residual NFPA, and reduced the recurrence of NFPA (33)(34)(35). These data suggest that it is of great importance to find strategies to predict recurrence.…”
Section: A B Cmentioning
confidence: 88%
“…Cabergoline, a dopamine agonist, is the first-line medication for prolactinoma [9][10][11] providing therapeutic effects regardless of sex, age, or initial prolactin value [12]. Cabergoline use is also associated with a favorable prognosis regarding visual acuity [13,14].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 In 10%–20% of cases, the tumors are unresponsive to conventional therapies. 3 Previous studies showed that dopamine agonist‐resistant prolactinoma might happen due to decreased dopamine two receptor (DR2) expression in tumor cells. 4 Aggressive pituitary tumors show various clinical manifestations as they have a tendency to grow, frequently recur, and are often irresponsive to standard treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Most macroprolactinomas are resolved with conventional therapies with dopamine agonists (such as cabergoline), surgery, and radiation 1,2 . In 10%–20% of cases, the tumors are unresponsive to conventional therapies 3 . Previous studies showed that dopamine agonist‐resistant prolactinoma might happen due to decreased dopamine two receptor (DR2) expression in tumor cells 4 .…”
Section: Introductionmentioning
confidence: 99%